2004
DOI: 10.1530/eje.0.151s055
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from the national cooperative growth study

Abstract: Objective: To review the National Cooperative Growth Study (NCGS), a national post-marketing surveillance program for children treated with biosynthetic growth hormone (GH) products from Genentech. Methods: Representative data are presented to summarize the extensive experience of the NCGS. This study is a multicenter, observational surveillance registry begun in 1985 in coordination with the release of the first recombinant DNA biosynthetic GH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…Main clinical signs are headaches, nausea, vomiting and visual changes. The prevalence of BIH in GHD patients on rhGH treatment is low (approximately 1.6 per 1,000 patients) [2,3,4,5]. Ocular examination of this patient revealed no abnormalities.…”
Section: Discussionmentioning
confidence: 88%
“…Main clinical signs are headaches, nausea, vomiting and visual changes. The prevalence of BIH in GHD patients on rhGH treatment is low (approximately 1.6 per 1,000 patients) [2,3,4,5]. Ocular examination of this patient revealed no abnormalities.…”
Section: Discussionmentioning
confidence: 88%
“…Therefore most of the currently available pharmacovigilance information has been obtained from large post-marketing studies sponsored by GH manufacturers. These studies have identified safety issues occurring during GH treatment, such as diabetes [15], slipped capital femoral epiphyses [16] and intracranial hypertension [17], but could not address issues occurring after treatment is stopped (such as neoplasms) as patients are mostly lost to follow-up once GH treatment is discontinued.…”
Section: Somatropinsmentioning
confidence: 99%
“…Further, even though there is regular reporting by all companies to the authorities, it is not apparent to the treating physician that the approved preparations can be considered equal as far as long-term safety is concerned. Until now, data about the long-term safety of rhGH are limited to publications on the prescription monitoring of two manufacturers (NCGS, KIGS/KIMS) [15,45,46,47,48], whose products can be considered the ‘leading substances’ as regards safety. Other manufacturers have not yet published results with data of comparable size.…”
Section: Pharmaceuticals Biosimilars and Approval Proceduresmentioning
confidence: 99%